(untitled) (Global Journal of Management and Business Research, 2018)
This paper proposes a procedure for the approximation of the transaction costs level in a firm as the difference between the total cost and the variable and fixed intrinsic costs It shows that these costs take their place in the heart of the costs leadership strategy The capitalistic intensity the recruitment policy and the training policy can then be used to act on the transactional inefficiency A theoretical model for the estimation of the contribution of each of those variables to the transaction costs is proposed